2008
DOI: 10.1021/jf802888w
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid as Antioxidant in Fish Muscle: Mechanism of Synergism with Endogenous Ascorbic Acid and α-Tocopherol

Abstract: In an emulsion of corn oil in water with the addition of caffeic acid (Caf-OH) and alpha-tocopherol (alpha-TOH), Caf-OH was found to be very active in delaying lipid oxidation without affecting significantly the kinetics for alpha-TOH degradation. In contrast, Caf-OH addition to fish muscle retarded both the degradation of endogenous alpha-TOH and the propagation of lipid oxidation, measured by peroxide value (PV) and thiobarbituric acid reactive substances (TBARS), with increasing effect with increasing Caf-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 41 publications
3
51
0
Order By: Relevance
“…Oil heated alone significantly lost the ability to scavenge radicals, which was in turn well maintained in the system with GCE (work in progress). The next step in this research direction should be therefore answering the question whether the synergistic effect of tocopherols with hydroxycinnamic acids [38], or the compounds arising from the degradation of oil and GCE components heated together have major influence on the high antioxidant activity of such a system. The obtained results in terms of relatively high antioxidant activity of heated systems confirmed the research of Charurin et al [39].…”
Section: Complex Model Systemsmentioning
confidence: 99%
“…Oil heated alone significantly lost the ability to scavenge radicals, which was in turn well maintained in the system with GCE (work in progress). The next step in this research direction should be therefore answering the question whether the synergistic effect of tocopherols with hydroxycinnamic acids [38], or the compounds arising from the degradation of oil and GCE components heated together have major influence on the high antioxidant activity of such a system. The obtained results in terms of relatively high antioxidant activity of heated systems confirmed the research of Charurin et al [39].…”
Section: Complex Model Systemsmentioning
confidence: 99%
“…Such factors include: consumption of high-PUFA or rancid diet; intake of mycotoxins, heavy metals, fungicides and pesticides; nutritional deficiency such as selenium; pathogenic infections; stress-related practices such as weaning, vaccination and transportation; exposure to ionizing radiation; animal's production status such as early lactation; and heat stress. Furthermore, once animals are slaughtered, there is concomitant loss of efficiency in the biological antioxidant system, which together with other post-slaughter conditions (Morrissey et al, 1998) result in the onset of lipid deterioration in muscle tissues and consequent oxidative rancidity in meat products (Iglesias et al, 2008).…”
Section: Effects Of Supplemental Antioxidants In Livestockmentioning
confidence: 99%
“…Example of such redox cooperation is the ability of terminal hydrophilic ascorbic acid to repair oxidized tocopheroxyl radical of vitamin E in order to allow vitamin E perform its antioxidant function again (Buettner, 1993). Similarly, Iglesias et al (2008) demonstrated that exogenous phenolic compound, grape procyanidins, had the ability to repair oxidized α-tocopherol and delay the depletion of ascorbic acid in the muscle tissues of fish. Thus, this highlights the importance of supplementing livestock with both groups of antioxidants to enhance duality of action which has proven to have synergistic effects.…”
Section: Effects Of Supplemental Antioxidants In Livestockmentioning
confidence: 99%
“…In this context, it has been found that natural antioxidants such as hydroxycinnamic acids could successfully delay lipid oxidation in minced fish muscle (Iglesias, Pazos, Andersen, Skibsted, & Medina, 2009;Medina, Gallardo, González, Lois, & Hedges, 2007;Medina, González, Iglesias, & Hedges, 2009). Particularly natural extracts from plants and herbs as pears, basil, and coffee, rich sources of caffeic acid and its derivative caffeic acid phenethyl ester, are being commercialized for their use as nutraceuticals and food supplements.…”
Section: Introductionmentioning
confidence: 99%